Financial derivatives, opacity, and crash risk: Evidence from large US banks - Dewally, Michaël; Shao, Yingying (Journal of Financial Stability, 2013)
We test how the use of financial derivatives affects banks’ informational structure and future stock performance based on a sample of large bank holding companies in the US. Using banks’ use of financial derivatives as a proxy for opacity, we find that high level use of interest rate and foreign exchange derivatives are associated with an increase in the synchronicity (R2) of stock price movements with the market index, which indicates less revelation of bank-specific information to the market. This finding is consistent with the prediction of the model developed by Wagner (2007). We document that superior corporate governance tempers these effects. Finally, we find that an increase in the opacity is significantly and positively related to an increase in banks’ future stock price crash risk.